Efek Tipe Kelahiran Terhadap Estrus Post-Partum Induk Sapi Bali Akseptor Inseminasi Buatan : Birt Type Effect on Post-Partum Etrus of Bali Cow Acceptor of Artificial Insemination - I Wayan Lanus Sumadiasa; Adji Santoso Dradjat; Lalu Ahmad Zaenuri; Rodiah Rodiah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Cases of dystocia is impact on delaying uterine involution, post-partum estrus and the next mating. Research has been carried out about type of birth process and its effect on post-partum estrus post-artificial insemination (AI) of Bali cows in Pujut District, Central Lombok Regency. The aim was to determine the effect of the type of birth process on post-partum estrus of cows. The research used descriptive method with the material were 40 Bali cows in 4 (four) villages, namely Pengengat, Teruwai, Mertak and Bangket Parak. The research variables were the type of birth process and post-partum estrus, as well as supporting variables such as the age of cow, body condition score (BCS), body weight, type of bull semen and days open. The data were statistically analyzed including the mean, standard deviation and percentage, followed by t-test. The results showed that 52.25% of Bali cows in Pujut District gave birth normally and 47.5% suffer light dystocia with birth assistance. The mean age of cows with dystocia was 29.53 ± 5.72 months by the BCS of 2.53, compared to 31.62 ± 5.61 months by the BCS of 2.81 in normal birth. The mean weight was 319.00 ± 29.72 kg compared to 342.81 ± 49.36 kg. The mean days open was 199.13 days compared to 195.67 days and post-partum estrus was 122.00 days compared to 105.00 days. In conclusion, the onset of post-partum estrus and days open in Bali cows that suffer light dystocia with birth assistance is longer than normal birth.